Coping with school failure in young people of CECYTE-BC - Zamudio Elizalde, Pedro Damián; Malaga Villegas, Sergio Gerardo (IE Revista de Investigación Educativa de la REDIECH, 2021)
In the field of knowledge about school permanence, there are limited studies that address strategies for coping with school failure. Research on this object follows a quantitative logic that limits the knowledge of specific behaviors that students put into practice in different settings. This article is derived from a study whose aim was to analyze the content of the social representation that third-grade students from CECyTE, Baja California, have about coping with school failure. From a qualitative approach, focus groups and interviews with high school students were developed. The results show that the transition from face-to-face education to online learning has produced an increase in the difficulty of adaptation at a psychological and behavioral level in the students. As a result of this, the participants of this study put into practice two coping styles. On the one hand, adaptive coping focused on solving the problem, from the participation of colleagues/friends, who guaranteed adaptation and psychological adjustment necessary to coping with failure. On the other hand, coping focused on emotions from the participation of family members.